2020
DOI: 10.1021/acs.jpclett.0c03070
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Rigidity Changes Ultraviolet Absorption: Effect of a Merocyanine Binder on G-Quadruplex Photophysics

Abstract: The urge to discover selective fluorescent binders to G-quadruplexes (G4s) for rapid diagnosis must be linked to understand the effect that those have on the DNA photophysics. Herein, we report on the electronic excited states of a bound merocyanine dye to c-Myc G4 using extensive multiscale quantum mechanics/molecular mechanics calculations. We find that the absorption spectra of c-Myc G4, both without and with the intercalated dye, are mainly composed of exciton states and mixed local/charge-transfer states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…At the same time, we are aware these sampling methods are not the only possibly way to generate initial condition for semi-classical non-adiabatic dynamics. Mixed classical-quantum methods have been highly promising to describe the shape of the UV absorption of dyes [ 40 , 41 ] or more complicated systems as transition metal complexes [ 39 ] or biological structures [ 42 ] in explicit solvent environments. It would be interesting to compare their applicability along non-adiabatic dynamics simulations.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, we are aware these sampling methods are not the only possibly way to generate initial condition for semi-classical non-adiabatic dynamics. Mixed classical-quantum methods have been highly promising to describe the shape of the UV absorption of dyes [ 40 , 41 ] or more complicated systems as transition metal complexes [ 39 ] or biological structures [ 42 ] in explicit solvent environments. It would be interesting to compare their applicability along non-adiabatic dynamics simulations.…”
Section: Resultsmentioning
confidence: 99%
“…A quantitative description, encompassing electronic relaxation and conformational motions in the entire G4, could be achieved by integrating molecular dynamics simulations. Such an approach, already applied for the determination of FC states in small G4, 29 should become affordable in the near future for the study of dynamical processes in larger systems.…”
mentioning
confidence: 99%
“…19 Among the specific DNA cavities there are a few of high biological significance, including i-motifs and G-quadruplexes (G4). 20,21 Both DNA structures are formed by stacking of Hoogsteen base pairs of cytosines or guanines, respectively. Their genetic relevance found in the expression of tumor cells, gene regulation, or cell division 22−24 stimulated an interest in finding selective biomarkers for these motifs.…”
mentioning
confidence: 99%
“…Recently, interactions of ThT with DNA have been reported. It was found that ThT exhibits a moderate emission enhancement in the presence of single- and double-stranded DNA, whereas a strong fluorescence could be detected upon ThT insertion into DNA cavities such as internal gaps or mismatch sites . Among the specific DNA cavities there are a few of high biological significance, including i-motifs and G-quadruplexes (G4). , Both DNA structures are formed by stacking of Hoogsteen base pairs of cytosines or guanines, respectively. Their genetic relevance found in the expression of tumor cells, gene regulation, or cell division stimulated an interest in finding selective biomarkers for these motifs.…”
mentioning
confidence: 99%